ANALYSIS OF CREATIVITY OF THE LEADING ARTISTS OF LAND-ART OF THE 20TH CENTURY - Гальчінська, О. С.; Гамалія, К. О.; Пашкевич, К. Л. (Art and Design, 2019)
Purpose of the article is to research the distinctive features of the works of leading artists of land-art of XXth century, the analysis of their place and contribution to the overall development of culture, as well as the impact of work on the creative artists today. Methodology. The methodological basis of the study is a systematic approach, methods of comparative-historical and art analysis. Results. Works of the leading artists of land-art of the XXth century were considered as part of the the goal. It is confirmed that the source of inspiration from artists of land art is nature, its phenomena, as well as human, his inner world and interaction with the environment. Defined the special significance of the information component in the land-art, as natural space and Earth's horizon is perceived by the artist as a coherent concrete semantic field. It was analysed that the concept of land-art combines a huge range of artistic projects created by the authors using different approaches, techniques and Ways of execution, but all of them are combined with common origin – to transform an element of a natural landscape into an art object. Methods of creation and presentation of viewer work in order to form a certain public opinion are researched. Scientific novelty consists in defining the peculiarities of the approaches and means for the creation of art objects of land-art as manifests by artists who turn to society in order to form public opinion and to attract attention to social and environmental problems of mankind. Practical significance is that the materials presented, their analysis and generalization can be used in scientific researches devoted to development of art of land art and also in definition of the creative influence of leading artists of land art of XX century on the activity of contemporary artists for further implementation in author's creative projects.